Respuesta :
Answer:
B. g(x) = RootIndex 3 StartRoot x minus 3 EndRoot + 4
Step-by-step explanation:
edg 2021 .. its correct
The equation that is graphed along with the parent function is [tex]g(x)=\sqrt[3]{x-3} +4[/tex]
The parent function is a cube root function, represented as:
[tex]f(x) = \sqrt[3]{x}[/tex]
First, the parent function is horizontally shifted right by 3 units
The rule of this transformation is:
[tex](x,y) \to (x - 3,y)[/tex]
So, we have:
[tex]f'(x) = \sqrt[3]{x - 3}[/tex]
Next, the transformed function is vertically shifted up by 4 units
The rule of this transformation is:
[tex](x,y) \to (x,y+4)[/tex]
So, we have:
[tex]g(x)=\sqrt[3]{x-3} +4[/tex]
Hence, the equation is [tex]g(x)=\sqrt[3]{x-3} +4[/tex]
Read more about function transformation at:
https://brainly.com/question/18249265